2022
DOI: 10.1177/00033197221110962
|View full text |Cite
|
Sign up to set email alerts
|

Regarding Comparison of Recent Practice Guidelines for the Management of Patients with Asymptomatic Carotid Stenosis

Abstract: We would like to alert readers to factual errors and omissions in a review recently published in Angiology by Paraskevas et al that may encourage continued overuse of invasive carotid artery procedures. 1 Further, most of these exist in other reviews as specifically indicated below. 2,3 1. A flawed interpretation is that some recent guidelines are suitably more restrictive in endorsing 'revascularisation' procedures for asymptomatic carotid stenosis (ACS) patients by specifying, 4,5 or at least considering, 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…5 Furthermore, a recent single-center study of a large academic institution in Southeastern United States reported a 2-year incidence of cerebrovascular events (stroke and transient ischemic attack [TIA]) as high as 11.5%. 6 Although it can be argued that the quality of medically intervention received by the AsxCS patients in this study was incompletely documented or that it did not address all risk factors, this pragmatic report suggests that ipsilateral annual TIA and stroke rates in patients with >70% AsxCS are not as low in “real-life” conditions as supported by Abbott et al 1 Finally, a 2021 population-based cohort study (Oxford Vascular Study) and a systematic review and meta-analysis demonstrated that the 5-year ipsilateral stroke risk for patients with AsxCS varied by the degree of stenosis from 0% for patients with 50–69% AsxCS to 14.6% for individuals with 70–99% AsxCS and up to 18.3% for patients with 80–99% AsxCS. 7 The oversimplification claimed by Abbott et al 1 that “ average annual ipsilateral stroke rates approximate only .8% with nonprocedural management ” is therefore not supported by any independent data.…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…5 Furthermore, a recent single-center study of a large academic institution in Southeastern United States reported a 2-year incidence of cerebrovascular events (stroke and transient ischemic attack [TIA]) as high as 11.5%. 6 Although it can be argued that the quality of medically intervention received by the AsxCS patients in this study was incompletely documented or that it did not address all risk factors, this pragmatic report suggests that ipsilateral annual TIA and stroke rates in patients with >70% AsxCS are not as low in “real-life” conditions as supported by Abbott et al 1 Finally, a 2021 population-based cohort study (Oxford Vascular Study) and a systematic review and meta-analysis demonstrated that the 5-year ipsilateral stroke risk for patients with AsxCS varied by the degree of stenosis from 0% for patients with 50–69% AsxCS to 14.6% for individuals with 70–99% AsxCS and up to 18.3% for patients with 80–99% AsxCS. 7 The oversimplification claimed by Abbott et al 1 that “ average annual ipsilateral stroke rates approximate only .8% with nonprocedural management ” is therefore not supported by any independent data.…”
mentioning
confidence: 60%
“…and meta-analysis demonstrated that the 5-year ipsilateral stroke risk for patients with AsxCS varied by the degree of stenosis from 0% for patients with 50-69% AsxCS to 14.6% for individuals with 70-99% AsxCS and up to 18.3% for patients with 80-99% AsxCS. 7 The oversimplification claimed by Abbott et al 1 that "average annual ipsilateral stroke rates approximate only .8% with nonprocedural management" is therefore not supported by any independent data.…”
mentioning
confidence: 97%
See 3 more Smart Citations